Clinical application, potential pharmacological targets and quality marker prediction of a TCM formulation used (Shenling Baizhu San) in the treatment of respiratory diseases - Gao, Zu; Wang, Tong; Fu, Liwen; Wu, Qiaolan; Wang, Yuan; Wu, Zhichun; Lu, Guangying; Ou, Chunxue; Zhao, Haijun; Yu, Huayun (Frontiers in Pharmacology, 2025)
Shenling Baizhu San (SLBZS) is a formulation of traditional Chinese medicine (TCM) recorded in the Song Dynasty medical book Taiping Huimin Heji Jufang (AD 1078–1085). It comprises eleven herbs: Ginseng Radix Et Rhizoma, Atractylodis Macrocephalae Rhizoma, Poria, Dioscoreae Rhizoma, Nelumbinis Semen, Coicis Semen, Lablab Semen Album, Amomi Fructus, Platycodonis Radix, Glycyrrhizae Radix Et Rhizoma, and Jujubae Fructus. SLBZS has been employed for over 900 years in the treatment of pulmonary and gastrointestinal disorders because of its qualities that enhance spleen function, tonify the lungs, supplement qi, and mitigate diarrhoea. This study meticulously examined and synthesised the clinical relevance and pharmacological mechanisms of SLBZS, concentrating on respiratory diseases, in response to the increasing volume of clinical data about SLBZS. Meanwhile, according to the five principles of Q-marker determination, including quality transmission and traceability, metabolites specificity, formula compatibility environment, association between metabolites and effectiveness, metabolites measurability, the potential quality markers (Q-markers) that SLBZS in the treatment of respiratory diseases were predicted. This study will provide additional clinical research, clarify pharmacological mechanisms, and set quality control criteria for SLBZS in the treatment of respiratory diseases.